Thickened Pituitary Stalk Associated with a Mass in the Sphenoidal Sinus: An Alarm to Suspect Hypophysitis by Immunoglobulin G4? - Batista, Rafael Loch; Ramos, Luciano Silva; Cescato, Valter Angelo; Musolino, Nina Rosa Castro; Borba, Clarissa Groberio; Silva, Gilberto Ochman; Moreno, Lilian Hupfeld; Cunha Neto, Malebranche Bernardo Carneiro (International Archives of Otorhinolaryngology, 2015)
Introduction Hypophysitis is a chronic inflammation of the pituitary gland of complex and still incompletely defined pathogenesis. It belongs to the group of non-hormone-secreting sellar masses, sharing with them comparable clinical presentation and radiographic appearance.Objectives Describe the case of immunoglobulin G4 (IgG4)-related hypophysitis presenting as a mass in the sphenoid sinus.Resumed Report A 40-year-old Brazilian man had a diagnosis of central diabetes insipidus since 2001 associated with pituitary insufficiency. Pituitary magnetic resonance imaging revealed a centered pituitary stalk with focal nodular thickening and the presence of heterogeneous materials inside the sphenoid sinus. The patient was treated with testosterone replacement therapy. Laboratory results revealed increased IgG4 serum.Conclusion IgG4-related hypophysitis should be considered in patients with pituitary insufficiency associated with sellar mass and/or thickened pituitary stalk. IgG4 serum measurement for early diagnosis of IgG4-related hypophysitis should be performed.
Keywords: pituitary diseases; hypopituitarism; sphenoid sinus